Understanding the Tendency of Media Users to Consume Fake News - Rouli Manalu; Tandiyo Pradekso; Djoko Setyabudi (FISIP Universitas Atma Jaya Yogyakarta, 2018)
This research investigates the ways in which different groups of media users have different tendencies in consuming and believing fake news. These tendencies are examined through: (1) analysis of association of age and income level with the pattern of media consumption; (2) analysis of association of age and income level with types of media that is perceived as the most trustworthy. Using systematic random sampling, this study examines 400 households in Semarang, Central Java, with level of confidence of 95%.